Positive electrode material, secondary battery, and electric device
By setting up a cladding layer of graft polymer, dielectric material and lithium salt on the surface of the ternary positive electrode active material, the interfacial side reaction and positive electrode material crushing problems when the sulfide solid electrolyte matches the ternary positive electrode material are solved, and the problem of positive electrode material breakage is achieved. Efficient ion and electron transport improves the Coulomb efficiency and cycling performance of secondary batteries.
Patent Information
- Application Number
- CN202411611357.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The electrochemical window of existing sulfide solid electrolytes is narrow, resulting in serious interface side reactions when matching the ternary positive electrode material, and the volume change of the positive electrode material during circulation leads to particle breakage and separation from the solid electrolyte.
The surface of the ternary positive electrode active material is provided with a cladding layer containing graft polymer, dielectric material and lithium salt. The graft polymer has excellent compatibility with the sulfide electrolyte material, and the dielectric material promotes the formation of a built-in electric field The lithium salt dissociates, increasing the ionic conductivity of the coating.
It effectively improves the contact and chemical stability between the positive electrode material and the sulfide electrolyte, prevents the positive electrode material from breaking, enhances the contact with the electrolyte material, and avoids disengagement, thereby improving the Coulomb efficiency and cycling performance of the secondary battery.
Smart Images

Figure BDA0005135025740000111 
Figure BDA0005135025740000112 
Figure BDA0005135025740000121
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode material, a secondary battery and an electrical device. Background Art
[0002] Secondary batteries, especially lithium-ion batteries, have certain safety issues. Lithium-ion battery fires and explosions occur from time to time. All-solid-state batteries replace the flammable, explosive and volatile electrolytes in lithium-ion batteries with non-flammable solid electrolytes, significantly improving the safety of the batteries.
[0003] At present, solid electrolytes mainly include oxides, sulfides, polymers and other types. Sulfide solid electrolytes have attracted widespread attention due to their advantages such as high ionic conductivity and moderate mechanical properties. However, the electrochemical window of sulfide solid electrolytes is narrow, and serious interfacial side reactions and the formation of space charge layers will occur when matching ternary positive electrode materials. In addition, the volume of the positive electrode will change during the cycle, resulting in particle breakage and separation from the solid electrolyte.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present application is to overcome the deficiencies of the prior art and provide a positive electrode material, a secondary battery and an electrical device, wherein the positive electrode material has excellent coulombic efficiency and cycle performance.
[0006] To achieve the above-mentioned purpose, the first aspect of the present application provides a positive electrode material, including a core and a coating layer arranged on the outer surface of the core, the core includes a ternary positive electrode active material, and the coating layer includes a grafted polymer, a dielectric material and a lithium salt; the main chain of the grafted polymer includes at least one of styrene-butadiene-styrene block copolymer, nitrile rubber, and styrene-isoprene-styrene copolymer, and the side chain of the grafted polymer includes a conductive polymer, and the conductive polymer includes at least one of polyparaphenylene, polypyrrole, polythiophene, polydiacetylene, and polyaniline.
[0007] As an embodiment of the present application, the thickness of the coating layer is 20 to 100 nm.
[0008] As an embodiment of the present application, the coating layer accounts for 1 to 2% of the total mass of the positive electrode material.
[0009] As an embodiment of the present application, the weight average molecular weight of the conductive polymer is 5,000 to 20,000.
[0010] As an embodiment of the present application, the grafting rate of the grafted polymer is 1 to 5%.
[0011] As an implementation scheme of the present application, at least one of the following (I) to (III) is satisfied:
[0012] (I) The mass percentage of the grafted polymer in the coating layer is 60-70%;
[0013] (II) The mass percentage of the dielectric material in the coating layer is 10 to 20%;
[0014] (III) The mass percentage of lithium salt in the coating layer is 10-20%.
[0015] As an embodiment of the present application, the dielectric material includes at least one of BaTiO3, LiNbO3, and NaNbO3.
[0016] As an embodiment of the present application, the lithium salt includes at least one of LiPF6, LiClO4, LiTFSI, LiFSI, and LiBOB.
[0017] As an embodiment of the present application, the ternary positive electrode active material includes a molecular formula of Li a Ni b Co c X d M e O2 compounds, wherein 0.9≤a≤1.1, 0.6≤b<1, 0 <c<0.4,0<d<0.4,0≤e≤0.1,b+c+d+e=1;
[0018] X includes at least one of Mn and Al; M includes at least one of Zr, Zn, Cu, Cr, Mg, Fe, V, W, Y, Nb, Ti, In, La, Ce, Sr, Sb, and B.
[0019] A second aspect of the present application provides a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material described above.
[0020] A third aspect of the present application provides an electrical device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electrical device.
[0021] The beneficial effects of the present application are as follows: the present application sets a coating layer comprising a grafted polymer, a dielectric material and a lithium salt on the surface of the ternary positive electrode active material. Among them, the grafted polymer has excellent compatibility with the sulfide electrolyte material, which can not only effectively improve the electron transmission rate, but also improve the contact between the positive electrode material and the sulfide electrolyte; and the dielectric material promotes the dissociation of the lithium salt by forming a built-in electric field inside the coating layer, thereby improving the ionic conductivity of the coating layer. The coating layer has high ionic conductivity, high electronic conductivity and flexibility at the same time, which is beneficial to improve the ion and electron transmission rate; in addition, it can effectively inhibit the occurrence of side reactions at the interface, improve the (electro)chemical stability between the positive electrode material and the sulfide electrolyte, prevent the positive electrode material from breaking, enhance the contact between the positive electrode material and the electrolyte material, and avoid its separation from the solid electrolyte, thereby effectively improving the coulombic efficiency and cycle performance of the secondary battery. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0023] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0024] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0025] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0026] The embodiment of the present application provides a positive electrode material, comprising a core and a coating layer arranged on the outer surface of the core, wherein the core comprises a ternary positive electrode active material, and the coating layer comprises a grafted polymer, a dielectric material and a lithium salt;
[0027] The main chain of the grafted polymer includes at least one of styrene-butadiene-styrene block copolymer (SBS for short), nitrile rubber (NBR for short), and styrene-isoprene-styrene copolymer (SIS for short), and the side chain of the grafted polymer includes a conductive polymer, and the conductive polymer includes at least one of polyparaphenylene, polypyrrole, polythiophene, polydiacetylene, and polyaniline.
[0028] The present application sets a coating layer comprising a grafted polymer, a dielectric material and a lithium salt on the surface of the ternary positive electrode active material. Among them, the grafted polymer has excellent compatibility with the sulfide electrolyte material, which can not only effectively improve the electron transmission rate, but also improve the contact between the positive electrode material and the sulfide electrolyte; and the dielectric material promotes the dissociation of the lithium salt by forming a built-in electric field inside the coating layer, thereby improving the ionic conductivity of the coating layer. The coating layer has high ionic conductivity, high electronic conductivity and flexibility at the same time, which is conducive to improving the ion and electron transmission rate; in addition, it can effectively inhibit the occurrence of side reactions at the interface, improve the (electro)chemical stability between the positive electrode material and the sulfide electrolyte, prevent the positive electrode material from breaking, enhance the contact between the positive electrode material and the electrolyte material, and avoid its separation from the solid electrolyte, thereby effectively improving the coulombic efficiency and cycle performance of the secondary battery.
[0029] In one embodiment, the thickness of the coating layer is 20 to 100 nm, for example, it can be 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or a range consisting of any two of these values. When the thickness of the coating layer is within this range, it has a good protective effect on the ternary positive electrode active material of the inner core, improves the stability of the material, and can obtain a coating layer with better barrier effect and kinetic effect.
[0030] The thickness of the coating layer has a well-known meaning in the art and can be tested using instruments and methods well-known in the art. For example, a transmission electron microscope (TEM for short) is used for analysis and testing to obtain a TEM image, and then the thickness of multiple (for example, more than 30) different positions is measured on the TEM image, and the average value is taken as the thickness of the coating layer.
[0031] In one embodiment, the coating layer accounts for 1 to 2% of the total mass of the positive electrode material, for example, it can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or a range consisting of any two of these values. When the mass of the coating layer is within this range, it is beneficial to improve the transmission rate of ions and electrons, ensure that active ions can smoothly migrate in and out of the coating layer, better improve ionic conductivity and electronic conductivity, and better protect the core material, improve the stability between the positive electrode material and the sulfide electrolyte, thereby further improving the coulombic efficiency and cycle performance.
[0032] In one embodiment, the coating layer accounts for the total mass of the positive electrode material by thermogravimetric analysis (such as TG spectrum). Since the positive electrode material and the coating layer material have different thermal decomposition temperatures, the coating layer and the positive electrode material will show a decrease in weight at different temperatures in the thermogravimetric test, thereby characterizing the mass proportion of the coating layer.
[0033] In one embodiment, the thickness of the coating layer is controlled by adjusting the solid content of the slurry prepared by the graft polymer, the dielectric material, and the lithium salt using a solvent.
[0034] In one embodiment, the weight average molecular weight of the conductive polymer is 5000 to 20000, for example, it can be 5000, 6000, 8000, 10000, 12000, 14000, 15000, 16000, 18000, 20000 or a range consisting of any two of these values. When the molecular weight of the conductive polymer is within this range, while ensuring high ionic conductivity and high electronic conductivity, it has good flexibility, can better inhibit the breakage of positive electrode material particles, improve its interface contact effect with the electrolyte material, avoid the separation of the positive electrode material and the electrolyte material, thereby further improving the coulombic efficiency and cycle performance.
[0035] In one embodiment, the grafting rate of the grafted polymer is 1 to 5%, for example, it can be 1%, 1.2%, 1.5%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two of these values. When the grafting rate of the grafted polymer is within this range, the grafted polymer has better flexibility and electronic conductivity, and can effectively reduce the volume expansion rate of the positive electrode material during the charge and discharge process, thereby further improving the coulombic efficiency and cycle performance.
[0036] In one embodiment, the mass percentage of the grafted polymer in the coating layer is 60-70%, for example, it can be 60%, 62%, 64%, 65%, 66%, 68%, 70% or a range consisting of any two values therein. When the mass percentage of the grafted polymer is within this range, the coating layer can better balance flexibility and ionic and electronic conductivity, thereby further improving coulombic efficiency and cycle performance.
[0037] In one embodiment, the mass percentage of the dielectric material in the coating layer is 10-20%, for example, it can be 10%, 12%, 14%, 15%, 16%, 18%, 20% or a range consisting of any two values therein. When the mass percentage of the dielectric material is within this range, the dielectric material promotes the dissociation of the lithium salt by forming an electric field inside, further improving the ionic conductivity of the coating layer, thereby further improving the coulombic efficiency and cycle performance.
[0038] In one embodiment, the mass percentage of the lithium salt in the coating layer is 10-20%, for example, it can be 10%, 12%, 14%, 15%, 16%, 18%, 20% or a range consisting of any two values therein. When the mass percentage of the lithium salt is within this range, it can better promote the ion transmission rate, improve ionic conductivity and electronic conductivity, thereby further improving the coulombic efficiency and cycle performance.
[0039] Among them, the mass percentage of the grafted polymer, dielectric material and lithium salt in the coating layer can be detected by the following method: the positive electrode plate in the secondary battery is removed, and then the plate is soaked with NMP, filtered, and dried to obtain the positive electrode material. Then the positive electrode material is tested by infrared spectroscopy to obtain the groups and lithium salts in the grafted polymer in the coating layer of the positive electrode material. Then the positive electrode material is tested by X-ray photoelectron spectroscopy (XPS) to analyze the dielectric material in the coating layer. Finally, the time-of-flight secondary ion mass spectrometry (TOS-SIMS) test can be performed to conduct quantitative research based on the fragment peak information of the grafted polymer, lithium salt and dielectric material.
[0040] In one embodiment, the dielectric material includes at least one of BaTiO3, LiNbO3, and NaNbO3.
[0041] In one embodiment, the lithium salt includes at least one of LiPF6, LiClO4, LiTFSI, LiFSI, and LiBOB.
[0042] In one embodiment, the ternary positive electrode active material includes a molecular formula of Li a Ni b Co c Xd M e O2 compounds, wherein 0.9≤a≤1.1, 0.6≤b<1, 0 <c<0.4,0<d<0.4,0≤e≤0.1,b+c+d+e=1;
[0043] X includes at least one of Mn and Al; M includes at least one of Zr, Zn, Cu, Cr, Mg, Fe, V, W, Y, Nb, Ti, In, La, Ce, Sr, Sb, and B.
[0044] In one embodiment, the method for preparing the grafted polymer comprises the following steps:
[0045] Put the main chain polymer and grafted monomer into a three-necked flask, add toluene solution, then add acetone solution containing initiator, stir magnetically, heat to 60-80°C, pass N2 protective gas, and react at constant temperature. After the reaction is completed, add anhydrous ethanol to produce a white flocculent precipitate. Remove the solvent by rotary evaporation and vacuum dry to obtain a white solid product. Finally, purify the product using a Soxhlet extractor to obtain a grafted polymer.
[0046] The grafting monomer includes at least one of p-toluene, pyrrole, thiophene, diacetylene and aniline.
[0047] The grafting rate of the grafted polymer = (total mass of the grafted polymer - the amount of the main chain polymer added) / the amount of the main chain polymer added × 100%. The grafting rate of the grafted polymer can be controlled by controlling the amount of the main chain polymer and the grafted monomer added.
[0048] In one embodiment, the mass ratio of the main chain polymer to the grafted monomer is (99:1) to (90:10).
[0049] In one embodiment, the initiator includes at least one of benzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and azobisisopropylimidazoline hydrochloride.
[0050] It should be noted that the present application does not impose any particular restriction on the amount of initiator added, as long as it is sufficient to initiate the reaction. Exemplarily, the initiator is 0.01% to 1% of the main chain polymer, for example, it can be 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1% or a range consisting of any two of these values.
[0051] In one embodiment, the method for preparing the positive electrode material comprises the following steps:
[0052] The grafted polymer, dielectric material and lithium salt are prepared into slurry with a solvent, and the ternary positive electrode material is added into the slurry, stirred evenly, and dried to obtain the positive electrode material.
[0053] The solvent includes at least one of toluene, xylene, acetone, ethanol, methanol, N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide, cyclopentane, tetrahydrofuran, 2-methyltetrahydrofuran, ethylene nitrate, ethylene carbonate, 1,4-butyrolactone and dimethylacetamide.
[0054] The solid content of the slurry is 1-60%, for example, it can be 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range consisting of any two of the values.
[0055] An embodiment of the present application provides a secondary battery, including a positive electrode plate, wherein the positive electrode plate includes the positive electrode material described above.
[0056] In one embodiment, the positive electrode plate further includes a sulfide solid electrolyte and a conductive agent.
[0057] In one embodiment, the sulfide solid electrolyte includes Li 10 GeP2S 12 、Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 , Li3PS4 or at least one of the following.
[0058] In one embodiment, the conductive agent includes one or more of vapor grown carbon fiber (VGCF), acetylene black (AB), carbon nanotube (CNT), and carbon black (superP).
[0059] In one embodiment, the secondary battery further includes a negative electrode plate.
[0060] In one embodiment, the negative electrode plate includes one or more of a lithium plate, an indium plate, and a LiIn alloy plate.
[0061] In one embodiment, the secondary battery further includes a solid electrolyte, and the solid electrolyte is located between the positive electrode plate and the negative electrode plate.
[0062] In one embodiment, the solid electrolyte comprises Li 10 GeP2S 12 、Li7P3S 11 、Li6PS5Cl、Li 5.5 PS4.5 Cl 1.5 , Li3PS4 or at least one of the following.
[0063] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0064] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0065] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.
[0066] An embodiment of the present application provides an electric device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.
[0067] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0068] The present application is further described below with specific embodiments:
[0069] Example 1
[0070] A preparation method of a secondary battery comprises the following steps:
[0071] (1) Preparation of grafted polymer: SBS and pyrrole were placed in a three-necked flask at a mass ratio of 95:5, and a toluene solution was added. Then, an acetone solution of 0.5% initiator benzoyl peroxide (BPO) was added to the total amount of SBS. The mixture was stirred magnetically, heated to 70°C, and N2 protective gas was passed through to react at a constant temperature. After the reaction was completed, anhydrous ethanol was added to produce a white flocculent precipitate. The solvent was removed by rotary evaporation, and the mixture was vacuum dried at 60°C to obtain a white solid product. Finally, the product was purified by a Soxhlet extractor to obtain a grafted polymer (SBS grafted polypyrrole polymer, grafting rate 3%).
[0072] (2) Preparation of positive electrode materials: SBS grafted polypyrrole polymer (grafting rate 3%), BaTiO3, and LiTFSI were added to a xylene solution in a mass ratio of 60:20:20 and stirred for 6 h. 0.8 Co 0.1 Mn 0.1O2 is added to the above mixed solution, LiNi 0.8 Co 0.1 Mn 0.1 The mass ratio of O2 to the mixed solution is 1:100. The mixture is stirred for 12 hours, and the solvent is dried to obtain the positive electrode material.
[0073] (3) The positive electrode material prepared above, Li6PS5Cl solid electrolyte, and VGCF were mixed in a planetary ball mill at a weight ratio of 80:19:1 to obtain a composite positive electrode powder.
[0074] (4) Secondary battery assembly and testing: Li6PS5Cl solid electrolyte was added to the mold battery, and then a pressure of 30MPa was applied for pre-pressing. The composite positive electrode powder prepared above was then added to one side of the electrolyte, and indium sheet (100μm) and lithium sheet (30μm) were added to the other side. A pressure of 400MPa was then applied to complete the assembly of the full secondary battery.
[0075] The preparation methods of the secondary batteries of Examples 2 to 21 and Comparative Examples 1 to 4 are basically the same as that of Example 1, and the changed parameters are shown in Table 1 for details; it should be noted that, in the examples listed in Table 1, unless otherwise specified, the variables are all single-factor variables.
[0076] Embodiments 2 to 5
[0077] The difference between Examples 2 to 5 and Example 1 is that Examples 2 to 5 adjust the thickness and mass percentage of the coating layer by adjusting the amount of the mixed solution and NCM811 added in step (2).
[0078] Embodiments 6 to 9
[0079] The difference between Examples 6 to 9 and Example 1 is that Examples 6 to 9 adjust the mass ratio of the grafted polymer, the dielectric material, and the lithium salt, thereby adjusting the mass percentage of the grafted polymer, the dielectric material, and the lithium salt in the coating layer.
[0080] Embodiments 10 to 13
[0081] The difference between Examples 10 to 13 and Example 1 is that Examples 10 to 13 use conductive polymers with different weight average molecular weights, thereby adjusting the weight average molecular weight of the conductive polymer.
[0082] Embodiments 14 to 17
[0083] The difference between Examples 14 to 17 and Example 1 is that Examples 14 to 17 adjust the amount of SBS and polypyrrole used to adjust the grafting rate of the grafted polymer.
[0084] Examples 18 to 21
[0085] The difference between Example 18 and Example 1 is that Example 18 uses thiophene to replace pyrrole.
[0086] The difference between Example 19 and Example 1 is that Example 19 uses aniline to replace pyrrole.
[0087] The difference between Example 20 and Example 1 is that Example 20 uses LiNbO3 to replace BaTiO3.
[0088] The difference between Example 21 and Example 1 is that Example 21 uses NaNbO3 to replace BaTiO3.
[0089] Comparative Example 1
[0090] A preparation method of a secondary battery comprises the following steps:
[0091] (1) The LiNi prepared above 0.8 Co 0.1 Mn 0.1 O2, Li6PS5Cl solid electrolyte, and VGCF were mixed in a planetary ball mill at a weight ratio of 80:19:1 to obtain a composite positive electrode powder.
[0092] (2) Secondary battery assembly and testing: Li6PS5Cl solid electrolyte was added to the mold battery, and then 30MPa pressure was applied for pre-pressing. Then the composite positive electrode powder prepared above was added to one side of the electrolyte, and indium sheet and lithium sheet were added to the other side. Then 400MPa pressure was applied to complete the assembly of the full secondary battery.
[0093] Comparative Example 2
[0094] A preparation method of a secondary battery comprises the following steps:
[0095] (1) Preparation of positive electrode materials: SBS, BaTiO3, and LiTFSI were added to a xylene solution in a mass ratio of 60:20:20 and stirred for 6 h. 0.8 Co 0.1 Mn 0.1 O2 was added to the mixed solution, stirred for 12 h, and the solvent was dried to obtain the positive electrode material.
[0096] (3) The positive electrode material prepared above, Li6PS5Cl solid electrolyte, and VGCF were mixed in a planetary ball mill at a weight ratio of 80:19:1 to obtain a composite positive electrode powder.
[0097] (4) Secondary battery assembly and testing: Li6PS5Cl solid electrolyte was added to the mold battery, and then a pressure of 30MPa was applied for pre-pressing. The composite positive electrode powder prepared above was then added to one side of the electrolyte, and indium and lithium sheets were added to the other side. A pressure of 400MPa was then applied to complete the assembly of the full secondary battery.
[0098] Comparative Example 3
[0099] A preparation method of a secondary battery comprises the following steps:
[0100] (1) Preparation of grafted polymer: SBS and polypyrrole were placed in a three-necked flask, toluene solution was added, and then an acetone solution containing initiator benzoyl peroxide (BPO) was added, magnetic stirring was applied, the temperature was raised to 70°C, N2 protective gas was passed, and the reaction was carried out at a constant temperature. After the reaction was completed, anhydrous ethanol was added to produce a white flocculent precipitate. The solvent was removed by rotary evaporation, and vacuum dried at 60°C to obtain a white solid product. Finally, the product was purified by a Soxhlet extractor to obtain a grafted polymer.
[0101] (2) Preparation of positive electrode materials: SBS grafted polypyrrole polymer (grafting rate 3%) and LiTFSI were added to a xylene solution at a mass ratio of 80:20 and stirred for 6 h. 0.8 Co 0.1 Mn 0.1 O2 was added to the mixed solution, stirred for 12 h, and the solvent was dried to obtain the positive electrode material.
[0102] (3) The positive electrode material prepared above, Li6PS5Cl solid electrolyte, and VGCF were mixed in a planetary ball mill at a weight ratio of 80:19:1 to obtain a composite positive electrode powder.
[0103] (4) Secondary battery assembly and testing: Li6PS5Cl solid electrolyte was added to the mold battery, and then a pressure of 30MPa was applied for pre-pressing. The composite positive electrode powder prepared above was then added to one side of the electrolyte, and indium and lithium sheets were added to the other side. A pressure of 400MPa was then applied to complete the assembly of the full secondary battery.
[0104] Comparative Example 4
[0105] A preparation method of a secondary battery comprises the following steps:
[0106] (1) Preparation of grafted polymer: SBS and polypyrrole were placed in a three-necked flask, toluene solution was added, and then an acetone solution containing initiator benzoyl peroxide (BPO) was added, magnetic stirring was applied, the temperature was raised to 70°C, N2 protective gas was passed, and the reaction was carried out at a constant temperature. After the reaction was completed, anhydrous ethanol was added to produce a white flocculent precipitate. The solvent was removed by rotary evaporation, and vacuum dried at 60°C to obtain a white solid product. Finally, the product was purified by a Soxhlet extractor to obtain a grafted polymer.
[0107] (2) Preparation of positive electrode materials: SBS grafted polypyrrole polymer (grafting rate 3%) and BaTiO3 were added to xylene solution in a mass ratio of 80:20 and stirred for 6 h. 0.8 Co 0.1 Mn 0.1 O2 was added to the mixed solution, stirred for 12 h, and the solvent was dried to obtain the positive electrode material.
[0108] (3) The positive electrode material prepared above, Li6PS5Cl solid electrolyte, and VGCF were mixed in a planetary ball mill at a weight ratio of 80:19:1 to obtain a composite positive electrode powder.
[0109] (4) Secondary battery assembly and testing: Li6PS5Cl solid electrolyte was added to the mold battery, and then a pressure of 30MPa was applied for pre-pressing. The composite positive electrode powder prepared above was then added to one side of the electrolyte, and indium and lithium sheets were added to the other side. A pressure of 400MPa was then applied to complete the assembly of the full secondary battery.
[0110] Table 1 Parameters of Examples 1 to 21
[0111]
[0112]
[0113] Performance Testing
[0114] The Xinwei battery testing system is used, with a voltage range of 3-4.25V. The charge and discharge rate tests include 0.1C, 0.33C, and 0.5C, and the cycle performance test is carried out at a rate of 0.33C.
[0115] Table 2 Performance test results of Examples 1 to 21 and Comparative Examples 1 to 4
[0116]
[0117]
[0118] As can be seen from Table 1, the positive electrode material described in the present application can significantly improve the coulombic efficiency and cycle performance, wherein the coulombic efficiency is ≥74%, and the 100 cycle capacity retention rate is ≥72%; since the present application sets a coating layer comprising a grafted polymer, a dielectric material and a lithium salt on the surface of the positive electrode ternary positive electrode active material, the coating layer has high ionic conductivity and electronic conductivity at the same time, which can effectively inhibit the side reaction at the interface, and can effectively improve the stability of the positive electrode material, prevent the positive electrode material from breaking, and enable the positive electrode material to be in close contact with the electrolyte material to avoid its separation from the solid electrolyte, wherein the conductive polymer has good compatibility with the electrolyte material and good flexibility, and can effectively improve the transmission rate of electrons, and the dielectric material promotes the lithium salt to improve the ionic conductivity of the coating layer by forming an electric field inside, thereby effectively improving the coulombic efficiency and cycle performance.
[0119] Comparative Examples 1 to 5 show that the coating layer thickness in the range of 20 to 100 nm has a significant effect. Within this range, the ion and electron transfer rate and the ability to inhibit side reactions can be well balanced, thereby further improving the coulombic efficiency and cycle performance.
[0120] By comparing Examples 1 and 6 to 9, it can be seen that when the mass ratio of the grafted polymer in the coating layer is 60 to 70%, the mass ratio of the dielectric material is 10 to 20%, and the mass ratio of the lithium salt is 10 to 20%, the effect is significant. Within this range, the ionic conductivity and electronic conductivity of the coating layer are optimal, thereby further improving the coulombic efficiency and cycle performance.
[0121] By comparing Examples 1 and 10 to 13, it can be seen that the preferred range of the weight average molecular weight of the conductive polymer is 5000 to 20000. Within this range, the electronic conductivity of the coating layer is the highest, thereby further improving the coulombic efficiency and cycle performance.
[0122] It can be seen from comparative examples 1 and 14 to 17 that the optimal range of the grafting rate of the polymer is 1 to 5%. Within this range, the grafted polymer has good compatibility with the electrolyte material and good flexibility, which can effectively improve the electron transmission rate, thereby further improving the coulombic efficiency and cycle performance.
[0123] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A positive electrode material, characterized in that: It comprises a core and a coating layer arranged on the outer surface of the core, wherein the core comprises a ternary positive electrode active material, and the coating layer comprises a grafted polymer, a dielectric material and a lithium salt; The main chain of the grafted polymer includes at least one of styrene-butadiene-styrene block copolymer, nitrile rubber, and styrene-isoprene-styrene copolymer, and the side chain of the grafted polymer includes a conductive polymer, which includes at least one of polyparaphenylene, polypyrrole, polythiophene, polydiacetylene, and polyaniline.
2. The positive electrode material according to claim 1, characterized in that The coating layer has a thickness of 20 to 100 nm.
3. The positive electrode material according to claim 1, characterized in that The coating layer accounts for 1-2% of the total mass of the positive electrode material.
4. The positive electrode material according to claim 1, characterized in that The weight average molecular weight of the conductive polymer is 5,000 to 20,000.
5. The positive electrode material according to claim 1, characterized in that The grafting rate of the grafted polymer is 1 to 5%.
6. The positive electrode material according to claim 1, characterized in that Satisfy at least one of the following (I) to (III): (I) The mass percentage of the grafted polymer in the coating layer is 60-70%; (II) The mass percentage of the dielectric material in the coating layer is 10 to 20%; (III) The mass percentage of lithium salt in the coating layer is 10-20%.
7. The positive electrode material according to claim 1, characterized in that The dielectric material comprises at least one of BaTiO3, LiNbO3, and NaNbO3; and / or The lithium salt includes at least one of LiPF6, LiClO4, LiTFSI, LiFSI, and LiBOB.
8. The positive electrode material according to claim 1, characterized in that The ternary positive electrode active material includes a molecular formula of Li a Ni b Co c X d M e O2 compounds, wherein 0.9≤a≤1.1, 0.6≤b<1, 0 <c<0.4,0<d<0.4,0≤e≤0.1,b+c+d+e=1; X includes at least one of Mn and Al; M includes at least one of Zr, Zn, Cu, Cr, Mg, Fe, V, W, Y, Nb, Ti, In, La, Ce, Sr, Sb, and B.
9. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material according to any one of claims 1 to 8.
10. An electrical device, characterized in that: The secondary battery according to claim 9 is included, and the secondary battery is used as a power supply for the electrical device.
Citation Information
Cited By
Positive electrode material, secondary battery and electric device
WO2026098223A1